2021
DOI: 10.1002/eat.23565
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders treatment experiences and social support: Perspectives from service seekers in mainland China

Abstract: Objective: This study explored treatment experiences and social support among individuals with eating disorders (EDs) in mainland China.Method: Subscribers of a Chinese online social media platform (WeChat) focused on EDs were invited to complete a screening questionnaire that included the Eating Disorder Diagnostic Scale for the DSM-5. Of the 116 questionnaire responses, 31 met inclusion criteria for follow-up interviews. Individuals who never sought treatment were not eligible for follow-up interviews, but p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The present findings suggest that interventions targeting transgender congruence and body appreciation may be promising potential avenues in the treatment of eating and body image disturbances in Chinese transgender adults. Importantly, there are limited well‐defined treatments existing for EDs in the Chinese context (Chen et al, 2021; Ma et al, 2021), a significant gap in treatment science that may reflect legislative gaps in mental health policy in China. Moreover, only relatively recently (2012) was national legislation passed in China addressing the mental health needs of its population (Phillips et al, 2013); however, this legislation excluded discussion of the mental health needs of sexual and gender minority populations.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings suggest that interventions targeting transgender congruence and body appreciation may be promising potential avenues in the treatment of eating and body image disturbances in Chinese transgender adults. Importantly, there are limited well‐defined treatments existing for EDs in the Chinese context (Chen et al, 2021; Ma et al, 2021), a significant gap in treatment science that may reflect legislative gaps in mental health policy in China. Moreover, only relatively recently (2012) was national legislation passed in China addressing the mental health needs of its population (Phillips et al, 2013); however, this legislation excluded discussion of the mental health needs of sexual and gender minority populations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the ED field, Asian countries resulted to be not represented despite the increasing trend of ED incidence in Asian countries which has been recently reported, mostly in China, also given its rapid economic growth [43]. The contribution of Asian countries to the ED research field would be much needed since the prevalence of EDs among female Chinese university students was found to be similar to that reported in Western countries [44]; however, it has been reported that only two specialized centers for the treatment of EDs are currently available in China thus potentially making difficult for patients being engaged in treatment and research studies [45]. However, as the study of EDs is still in its infancy in non-Western countries, it is possible that many publications in other languages are not always available in the online libraries used and are not published in journals in the first quartile.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the current study illustrates, individuals’ perceptions of mental health services cannot be considered in the absence of their cultural context. In fact, Western conceptualizations of psychopathology may be discrepant from how the Chinese public view psychological symptoms and how they should be discussed and treated (Ma, Capobianco, et al, 2020; Ma et al, 2021) Because stress and coping cannot be examined in the absence of cultural context (Wong & Wong, 2006) and psychological services are more beneficial when cultural norms and values are considered (G. C. N. Hall et al, 2016), international researchers and practitioners should attend to the cultural context and knowledge generated from local individuals with lived experience when working with mental health professionals in China.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the current study illustrates, individuals' perceptions of mental health services cannot be considered in the absence of their cultural context. In fact, Western conceptualizations of psychopathology may be discrepant from how the Chinese public view psychological symptoms and how they should be discussed and treated (Ma, Capobianco, et al, 2020;Ma et al, 2021) Because stress and coping cannot be examined in the absence of cultural context (Wong & Wong, 2006) and psychological services are more beneficial when cultural norms and values are considered (G. C. N. Hall et al, 2016), international researchers and practitioners should attend to the cultural context and knowledge As mental health research and practice is increasingly carried out globally, mental health professionals need to attend to the tendency of overgeneralizing research findings based on predominantly Western samples and using Western psychological frameworks as the norm or default. Future mental health research would benefit from incorporating more diverse perspectives and taking collaborative approaches that allow advancement of the field with recognition of both the limitations and merits of locally generated knowledge.…”
Section: Implications In Global Mental Healthmentioning
confidence: 99%